2015
DOI: 10.3389/fnins.2015.00250
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of incentivized dishonesty by disgust facial expressions

Abstract: Disgust modulates moral decisions involving harming others. We recently specified that this effect is bi-directionally modulated by individual sensitivity to disgust. Here, we show that this effect generalizes to the moral domain of honesty and extends to outcomes with real-world impact. We employed a dice-rolling task in which participants were incentivized to dishonestly report outcomes to increase their potential final monetary payoff. Disgust or control facial expressions were presented subliminally on eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
(57 reference statements)
2
7
0
Order By: Relevance
“…Furthermore, going beyond the prior work (Liu et al, 2015), in this study we statistically compared the emotional effects on spatial attention between individuals with low and high disgust sensitivity. It is known that responses to disgust elicitors vary considerably among individuals (Borg, de Jong, Renken, & Georgiadis, 2013;Lim et al, 2015;Sherlock, Zietsch, Tyber, & Jern, 2016). Our results revealed that the intensity of attention modulation by disgust (reflected by attentional bias scores of the N1 and P3a amplitudes) significantly correlated with self-report measures of disgust sensitivity (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Furthermore, going beyond the prior work (Liu et al, 2015), in this study we statistically compared the emotional effects on spatial attention between individuals with low and high disgust sensitivity. It is known that responses to disgust elicitors vary considerably among individuals (Borg, de Jong, Renken, & Georgiadis, 2013;Lim et al, 2015;Sherlock, Zietsch, Tyber, & Jern, 2016). Our results revealed that the intensity of attention modulation by disgust (reflected by attentional bias scores of the N1 and P3a amplitudes) significantly correlated with self-report measures of disgust sensitivity (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…The masked version of the dot-probe task was designed according to previous studies (Carlson et al, 2014;Carlson et al, 2013;Lim, Ho, & Mullette-Gillman, 2015;Liu et al, 2015;D. Zhang, Wang, Luo, & Luo, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently specified this effect, showing that the direction and degree of the modulation of moral judgments by disgust priming is dependent on the sensitivity of an individual to disgusting stimuli – that presentation of disgust facial expressions result in increased acceptability of utilitarian actions for individuals with high disgust sensitivity and reduced acceptability for those with low sensitivity 6 . Further, we have replicated and extended this finding by showing that this effect extends to incentive-compatible choices in a economic task (extending from the moral foundation of personal harm to honesty), in which the disgust primes resulted in increased likelihood of cheating behavior in participants with high sensitivity and decreased likelihood of cheating for those with low sensitivity 5 . Intriguingly, combining the data across these studies demonstrated that the function was indistinguishable across these tasks, suggesting that the same cognitive and neural mechanisms may be at play in both.…”
Section: Introductionsupporting
confidence: 57%
“…In three previous behavioral experiments 5 , 6 , we found that the average individual change in acceptability ratings due to emotional priming was correlated with individual differences in disgust sensitivity (DS-R). Within the current smaller fMRI sample, this relationship was not significant (r = 0.02, p = 0.94).…”
Section: Resultsmentioning
confidence: 80%